HUBUNGAN KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DENGAN MOTIVASI KERJA GURU DI SMK MULTI KARYA MEDAN - Purba, Anna Wati Dwi (JURNAL DIVERSITA, 2016)
This research was conducted in order to determine whether there is a relationship between interpersonal communication with the school principal motivation of teachers working in vocational Multi Karya Medan. The method used in this research is quantitative research methods. Subjects in this study were teachers who worked in SMK Karya Multi Terrain, totaling 47 people. The scale used in this study is the scale of interpersonal communication in Girsang by Cooper (2006), which amounts to 40 item, whereas the scale of work motivation according Aldefer in Wijono (1994), which consist of 40 item. Interpersonal communication scale reliability rbt = 0722, work motivation scale reliability rbt = 0686. Data analysis techniques used in this study is the product moment correlation analysis technique used to analyze the relationship between the independent variables and the dependent variable. By using SPSS version 18.0. From the analysis it is known that there is a significant positive relationship between Interpersonal Communication at Work Motivation, where r xy = 0677; p = 0.000 <0.010. Other results obtained from this study is the interpersonal communication is high because the average value empirically obtained by the 112 148 greater than the average value of the hypothetical of 80 with the difference that exceeds the value of SD or SB magnitude of 12,900, while the work motivation is high because the average value obtained by the empirical 114 340 greater than the average value of the hypothetical is 82.5 with a difference exceeding the value of the magnitude of SD or SB 11 493. From these results, the hypothesis are accepted.